2020
DOI: 10.1259/bjr.20200874
|View full text |Cite
|
Sign up to set email alerts
|

Adding contrast-enhanced ultrasound markers to conventional axillary ultrasound improves specificity for predicting axillary lymph node metastasis in patients with breast cancer

Abstract: Objective: To evaluate the diagnostic performance of contrast-enhanced ultrasound (CEUS) combined with conventional ultrasound (US) of axillary lymph nodes (ALNs) in predicting metastatic ALNs in patients with breast cancer. Methods: This retrospective study included 259 patients with breast cancer who underwent conventional US and CEUS. The parameters and patterns evaluated on conventional US included short axis diameter (S), long axis/short axis (L/S) ratio, cortical thickness, resistive index (RI), lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The value of CEUS in the diagnosis and evaluation of the curative effect of breast cancer has been recognized ( 23 , 24 ). Our research revealed that malignant neoplasms usually showed high heterogeneous enhancement, unclear enhancement boundary, perfusion defect, perforating vessels, large post-enhanced area, and high PI and tAUC values.…”
Section: Discussionmentioning
confidence: 99%
“…The value of CEUS in the diagnosis and evaluation of the curative effect of breast cancer has been recognized ( 23 , 24 ). Our research revealed that malignant neoplasms usually showed high heterogeneous enhancement, unclear enhancement boundary, perfusion defect, perforating vessels, large post-enhanced area, and high PI and tAUC values.…”
Section: Discussionmentioning
confidence: 99%
“…Rich blood flow is an indicator of the faster growth and higher metabolism of malignant tumors over benign tumors (26,27). Abnormal lymph nodes on US images, a possible indicator of high tumor aggressiveness, could also help detect breast cancers, as previously reported (28,29).…”
Section: Discussionmentioning
confidence: 78%
“…Although CUE has high sensitivity in the diagnosis of breast cancer, some previous studies have found that the accuracy, sensitivity, and specificity of ultrasound in diagnosing ALN metastasis is not so high ( 51 53 ). The concept of SWE was first proposed by Sarvazyan et al in 1998 ( 54 ).…”
Section: Discussionmentioning
confidence: 96%